Size-Resolved Fluorescence Underscores Negligible Interaction of Dissolved Organic Matter During Conservative Mixing in a Large Boreal River - Xue, Jin-Ping; Cuss, Chad W.; Wang, Yu; Javed, Muhammad B.; Noernberg, Tommy; Pelletier, Rick; Shotyk, William (Frontiers in Environmental Chemistry, 2022)
Although river mixing occurs widely in nature, the corresponding evolution of dissolved organic matter (DOM) composition remains poorly understood. Here, surface water samples were collected at multiple transects in the lower Athabasca River (LAR) under base-flow conditions. Asymmetric flow field-flow fractionation (AF4) coupled to online excitation-emission measurements (EEMs) and parallel factor analysis (PARAFAC) were utilized to investigate the size distribution of fluorescent DOM components during river mixing and the corresponding variation in size-resolved fluorescence. The majority of fluorescent components occurred at 0.810 and 1.170 kDa, reflecting the small size of the DOM molecules with maximum fluorescence. The loadings of fluorescence normalized to absorbance at 254 nm (A254) were highest for most terrestrial humic-like components, followed by the microbial humic-like component, and the protein-like components. Differences in size-resolved fluorescence were observed between DOM in humic-rich tributaries and in the mainstem of the LAR upstream of tributary inputs. The trend of variations in the A254-normalized PARAFAC loadings of terrestrial humic-like components also illustrates conservative mixing of aromatic-rich terrestrial DOM across size fractions in the LAR. From a molecular point of view, the mixing of fluorescent DOM occurred linearly and simultaneously across sizes without any evidence of aggregation, sedimentation, or changes in the fluorescence or concentration of any size fraction over the > 60 km required for complete mixing of the river and its tributaries. Overall, this study provides insights into the size characteristics of fluorescent components of DOM and their conservative mixing behavior in large boreal rivers.